Optimalisasi Managemen dan Pemasaran Digital Usaha Kecil Ibu Rumah Tangga - Yuliatin Azizah; Tamriatin Hidayah (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2022)
Welfare for people who have the main income as farmers can be assisted by housewives to boost family income with small businesses. These small businesses need to be given guidance and assistance so that their business develops according to the progress of the times. By collecting business data, it is possible to obtain business data for mothers and then sort out businesses that have the intention of developing a business. With the method of counseling business owners by visiting business places one by one to provide motivation in developing a business so that people who were not aware that business could develop finally have the will and motivation. Furthermore, business management training with digital marketing pressure points was held. As a result, the businesses owned by housewives are more developed by recognizing digital businesses but are still weak in planning management and recording results or finances. So that the follow-up plan for this assistance is training on business and financial records. It is even more important to collaborate with a digital financial recording application platform that is easier, safer and user-friendly for the community so that businesses can develop.